The effect of a secondary task on drivers' gap acceptance and situational awareness at junctions. Issue 2 (1st February 2021) - Robbins, Chloe J.; Rogers, James; Walton, Sophie; Allen, Harriet A.; Chapman, Peter
Abstract: The current studies explored the roles of the visuospatial and phonological working memory subsystems on drivers' gap acceptance and memory for approaching vehicles at junctions. Drivers' behaviour was measured in a high-fidelity driving simulator when at a junction, with, and without a visuospatial or phonological load. When asked to judge when to advance across the junction, gap acceptance thresholds, memory for vehicles and eye movements were not different when there was a secondary task compared to control. However, drivers' secondary task performance was more impaired in the visuospatial than phonological domain. These findings suggest that drivers were able to accept impairment in the secondary task while maintaining appropriate safety margins and situational awareness. These findings can inform the development of in-car technologies, improving the safety of road users at junctions. Practitioner summary: Despite research indicating that concurrent performance on working memory tasks impairs driving, a matched visuospatial or phonological memory load did not change drivers' gap acceptance or situational awareness at junctions. Drivers displayed appropriate compensatory behaviour by prioritising the driving task over the visuospatial secondary task. Abbreviations: ROW: right of way; RIG: random time interval generation